The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17977/um023v6i12017p076
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Pelatihan Manajemen Stres Pada Mahasiswa

Abstract: AbstrakPenelitian ini dilakukan untuk mengetahui efektivitas pelatihan manajemen stress. Hal ini merupakan tindakan pencegahan untuk meminimalkan efek negatif dari stres. Pengumpulan data dilakukan dengan menggunakan soal terkait materi yang disampaikan selama pelatihan. Penelitian ini bersifat quasi eksperimen berupa one group pre test, post test design. Pelatihan dilakukan selama dua hari dengan subyek penelitian sebanyak 80 mahasiswa yang berasal dari berbagai fakultas di Universitas Negeri Malang. Mereka d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
7
0
5
Order By: Relevance
“…Another study found that management training stress on students is very effective. Students can understand the material on stress management delivered and practice independently (14). This is because stress can be positive or negative depending on the perception of the person who feels it.…”
Section: The Stress Level Of Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that management training stress on students is very effective. Students can understand the material on stress management delivered and practice independently (14). This is because stress can be positive or negative depending on the perception of the person who feels it.…”
Section: The Stress Level Of Respondentsmentioning
confidence: 99%
“…If the ability to deal with stress is not good enough, and the demands are very high, the stress will increase (15). Management training stress in medical students is essential to make the students more skilled in coping with stress in the era of online learning so that it can achieve the desired results (14). Some ways to reduce stress include, among others, consuming healthy and nutritious foods, maintaining physical fitness, doing breathing exercises, doing fun activities, taking a vacation, avoiding bad habits, planning daily routines, keeping plants and animals, sparing time for oneself or families, and avoiding loneliness.…”
Section: The Stress Level Of Respondentsmentioning
confidence: 99%
“…Sebuah penelitian dilakukan oleh Hakim, Tantiani, Shanti (2017) tentang Efektifitas Pelatihan Manajemen Stres Pada Mahasiswa dengan subyek penelitian sebanyak 80 mahasiswa yang berasal dari berbagai fakultas di Universitas Negeri Malang. Mereka diukur saat pre test, diberi perlakuan, kemudian diberi post test.…”
Section: Gambar 1 Scatter Plot Hubungan Stres Akademik Dengan Kualitunclassified
“…Hasil pencarian yang tidak diproses (15) PENDAHULUAN Manusia memiliki fase dalam kehidupan, mulai dari bayi, anak-anak, remaja, dewasa dan pada fase terakhir adalah lansia (lanjut usia). Remaja merupakan fase paling penting dalam kehidupan manusia di mana remaja menggambarkan fase kehidupan yang menjadi masa transisi dari masa anak-anak menuju masa dewasa.…”
Section: Pencarian Literaturunclassified
“…3) Tahap ketiga yaitu mempraktekkan teknik manajemen stres dalam masalah dalam kehidupan dan menilai keefektifannya. 15 Hasil analisis menyatakan bahwa teknik manajemen stres memiliki banyak ragam. Teknik pertama adalah Problem Focused Coping.…”
Section: Pembahasanunclassified